1996
DOI: 10.1037/0022-006x.64.3.435
|View full text |Cite
|
Sign up to set email alerts
|

An approach to psychotherapy change process research: Introduction to the special section.

Abstract: This special section has a dual focus. One is on psychotherapy change research. The other is to explicate an approach to develop a program of research that builds on 2 aspects of scientific discovery: decomposition of observed phenomena and localization of specific elements that may combine to produce a complex whole. These aspects are considered within an ordered framework of 8 steps in the development and testing of a model, moving from discovery to model construction, validation, and prediction of complex o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 11 publications
6
86
0
5
Order By: Relevance
“…Indeed, 91% of the study sample met criteria for a mood, anxiety, disruptive behavior, alcohol, and/or substance use disorder, which is much higher than rates in community samples. In comparison, Newman et al (1996) followed a community based birth cohort of 1,037 children into young adulthood and found that the prevalence of DSM mental disorders ranged from 22% in early adolescence (13 years old) to 41% in late adolescence (18 years old). Additionally, in the present sample, 94% of adolescents reported some SI, with approximately 57% reporting clinically significant SI (SIQ > 41; Reynolds, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 91% of the study sample met criteria for a mood, anxiety, disruptive behavior, alcohol, and/or substance use disorder, which is much higher than rates in community samples. In comparison, Newman et al (1996) followed a community based birth cohort of 1,037 children into young adulthood and found that the prevalence of DSM mental disorders ranged from 22% in early adolescence (13 years old) to 41% in late adolescence (18 years old). Additionally, in the present sample, 94% of adolescents reported some SI, with approximately 57% reporting clinically significant SI (SIQ > 41; Reynolds, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Most content analyses of what patients and therapists actually discuss in psychotherapy are restricted to qualitative efforts that can be rich in content but by their nature are small in scope (e.g., Greenberg & Newman, 1996). While qualitative work remains important, the labor intensiveness of closely reading session content means that the vast majority of psychotherapy data is never analyzed.…”
Section: Many Distinctions But Is There a Difference?mentioning
confidence: 99%
“…Further, reviews of the neurotherapy literature, from those in the field and from outside the field, reinforce those models by holding them up as a unitary standard (Arnold, 1995;Arns & Lyle, 2010;Heinrich, Gevensleben, & Strehl, 2007;Masterpasqua & Healey, 2003). Greenberg and Newman (1996) maintained that multiple research approaches add to the literature and different approaches fit different problems. With careful examination of the studied phenomena, it is apparent that the pharmacological model may not be the best fit to assess the efficacy and effectiveness of neurofeedback.…”
Section: In Search Of An Accurate Modelmentioning
confidence: 93%